FROM THE NEUROBIOLOGY OF EXTINCTION TO IMPROVED CLINICAL TREATMENTS - Filomene G. Morrison; Kerry J. Ressler (2013)
The neural circuitry underlying the fear response is extremely well conserved across mammalian species, which has allowed for the rapid translation of research findings in rodent models of fear to therapeutic interventions in human populations. Many aspects of exposure-based psychotherapy treatments in humans, which are widely used in the treatment of PTSD, panic disorder, phobias, and other anxiety disorders, are closely paralleled by extinction training in rodent fear conditioning models. Here, we discuss how the neural circuitry of fear learning and extinction in rodent animal models may be used to understand the underlying neural circuitry of fear-related disorders, such as PTSD in humans. We examine the factors that contribute to the pathology and development of PTSD. Next, we will review how fear is measured in animal models using classical Pavlovian fear conditioning paradigms, as well as brain regions such as the amygdala, which are involved in the fear response across species. Finally, we highlight the following three systems involved in the extinction of fear, all of which represent promising avenues for therapeutic interventions in the clinic: (1) the role of the glutamatergic N-methyl-d-aspartate (NMDA) receptor, (2) the role of the brain-derived neurotrophic factor (BDNF)–tyrosine kinase B (TrkB) induced signaling pathway, and (3) the role of the renin-angiotensin system. The modulation of pathways underlying fear learning and extinction, such as the ones presented in this review, in combination with extinction-based exposure therapy, represents promising avenues for therapeutic intervention in the treatment of human fear related disorders.